Design and Development Early Detection of Neurodegenerative Disease Using IoT Technology - Safira Faizah; Dian Nugraha; M. N. Mohammed; Muhammad Irsyad Abdullah (Teknik Informatika Universitas Pamulang, 2023)
Parkinson's disease (PD) stands as one of the most prevalent conditions, impacting approximately 6.3 million individuals globally. This disorder becomes even more complex due to commonly associated non-motor symptoms like depression, cognitive impairments, and disruptions in sleep patterns. The root of PD remains largely unclear as a significant portion of cases lack a specific cause. In the initial phases of the illness, prominent indicators encompass tremors, rigidity, slowed motion, and difficulties in mobility. Presently, patients are obligated to have appointments with their medical practitioner at intervals of six months to a year, typically for brief consultations. The visit to the medical facility offers a limited glimpse into the patient's state, frequently failing to capture the day-to-day obstacles they encounter. The current evaluation methods are insufficient in comprehending this matter. This highlights the significance of promptly identifying PD, as it allows for the early implementation of treatment measures and management tactics. Additionally, this suggested approach contributes to the enhancement of human life within the healthcare framework and holds the potential to identify Parkinson’s disease swiftly and precisely.